Lutzomyia longipalpis Saliva Triggers Lipid Body Formation and Prostaglandin E(2) Production in Murine Macrophages - Araújo-Santos, Théo (Public Library of Science, 2010)
BACKGROUND: Sand fly saliva contains molecules that modify the host's hemostasis and immune responses. Nevertheless, the role played by this saliva in the induction of key elements of inflammatory responses, such as lipid bodies (LB, also known as lipid droplets) and eicosanoids, has been poorly investigated. LBs are cytoplasmic organelles involved in arachidonic acid metabolism that form eicosanoids in response to inflammatory stimuli. In this study, we assessed the role of salivary gland sonicate (SGS) from Lutzomyia (L.) longipalpis, a Leishmania infantum chagasi vector, in the induction of LBs and eicosanoid production by macrophages in vitro and ex vivo. METHODOLOGY/PRINCIPAL FINDINGS: Different doses of L. longipalpis SGS were injected into peritoneal cavities of C57BL/6 mice. SGS induced increased macrophage and neutrophil recruitment into the peritoneal cavity at different time points. Sand fly saliva enhanced PGE(2) and LTB(4) production by harvested peritoneal leukocytes after ex vivo stimulation with a calcium ionophore. At three and six hours post-injection, L. longipalpis SGS induced more intense LB staining in macrophages, but not in neutrophils, compared with mice injected with saline. Moreover, macrophages harvested by peritoneal lavage and stimulated with SGS in vitro presented a dose- and time-dependent increase in LB numbers, which was correlated with increased PGE(2) production. Furthermore, COX-2 and PGE-synthase co-localized within the LBs induced by L. longipalpis saliva. PGE(2) production by macrophages induced by SGS was abrogated by treatment with NS-398, a COX-2 inhibitor. Strikingly, SGS triggered ERK-1/2 and PKC-α phosphorylation, and blockage of the ERK-1/2 and PKC-α pathways inhibited the SGS effect on PGE(2) production by macrophages. CONCLUSION: In sum, our results show that L. longipalpis saliva induces lipid body formation and PGE(2) production by macrophages ex vivo and in vitro via the ERK-1/2 and PKC-α signaling pathways. This study provides new insights regarding the pharmacological mechanisms whereby L. longipalpis saliva influences the early steps of the host's inflammatory response.